The Epidemiology of Revision Total Knee Arthroplasty - Tarazi, John M.; Chen, Zhongming; Scuderi, Giles R.; Mont, Michael A. (The Journal of Knee Surgery, 2021)
With an expected increase in total knee arthroplasty (TKA) procedures, revision TKA (rTKA) procedures continue to be a burden on the United States health care system. The evolution of surgical techniques and prosthetic designs has, however, provided a paradigm shift in the etiology of failure mechanisms of TKA. This review can shed light on the current reasons for revision, which may lead to insights on how to improve outcomes and lower future revision risks. We will primarily focus on the epidemiology of rTKA in the present time, but we will also review this in the context of various time periods to see how the field has evolved. We will review rTKAs: 1) prior to 1997; 2) between 1997 and 2000; 3) between 2000 and 2012; and 3) in the modern era since 2012. We will further subdivide each of the sections into reasons for early (first 2 years after index procedure) versus late revisions (greater than 2 years after index procedure). In doing so, it was determined that prior to 1997, the most prevalent causes of failure were infection, patella failure, polyethylene wear, and aseptic loosening. After a major shift of failure mechanisms was described by Sharkey et al, polyethylene wear and aseptic loosening became the leading causes for revision. However, with the improved manufacturing technology and implant design, polyethylene wear was replaced with aseptic loosening and infection as the leading causes of failure between 2000 and 2012. Since that time, in the modern era of TKA, mechanical loosening and infection have taken over the most prevalent causes for failure. Hopefully, with continued developments in component design and surgical techniques, as well as increased focus on infection reduction methods, the amount of rTKA procedures will decline.
Keywords: revision total knee arthroplasty; epidemiology; TKA failure